Mycobacterium tuberculosis Induced Osteoblast Dysregulation Involved in Bone Destruction in Spinal Tuberculosis - Ma, Wenxin; Jin, Weidong; He, Xijing; Sun, Yuhang; Yin, Huquan; Wang, Zili; Shi, Shiyuan (Frontiers in Cellular and Infection Microbiology, 2022)
Disturbance of bone homeostasis caused by Mycobacterium tuberculosis (Mtb) is a key clinical manifestation in spinal tuberculosis. However, the complete mechanism of this process has not been established and effective treatment target is not existing. Increasing evidence shows abnormal osteoclastgenesis triggered by imbalance of receptor activator of NF-κB ligand (RANKL)/osteoprotegerin (OPG) axis may play a key role in disturbance of bone homeostasis. Previous studies reported RANKL is strongly activated in spinal TB patients, however the OPG level of spinal TB patients was not investigated in previous studies. In this study, we investigated the OPG levels of spinal TB patients and dysregulation of osteoblasts caused by Mtb infection. Inhibition of mce4a gene of Mtb by an antisense LNA GapmeRs (Mce4a-ASO) were also investigated. Analysis of serum OPG levels in clinical samples shows the OPG levels is significantly decreased in spinal TB patients compared to none-TB patients’ group. The intrinsic of Mtb in osteoblasts, the known major source of OPG, was investigated using GFP-labeled Mycobacterium H37Ra (H37RaGFP). Cell-associated fluorescence measurement shows that Mtb can efficiently enter osteoblast cells. And Mtb infection caused dose-dependently increase of cd40 mRNA expression and cytokine (IL-6) secretion in osteoblast cells. Ligation of CD40 by soluble CD154 reversed the increased IL-6 secretion. This means induced CD40 is functional. Considering the interaction between Cd154-expressing T lymphocytes and bone-forming osteoblast cells play pivotal role in bone homeostasis, Cd40 molecule might be a strong candidate for mediating target for treatment of the bone destruction in spinal TB. Additionally, we also found Mce4a-ASO could dose-dependently inhibition of Mce4a gene of Mtb , reverse the decrease the IL-6 secretion and impaired OPG secretion caused by Mtb infection in osteoblast cells. Taken together, the current finding provides the break-through ideas for therapeutic agent development in Spinal TB.